SEBUAH ANALISA KEMAMPUAN SISWA TAHUN KEDUA DI SMAN 1 BANTAN KABUPATEN BENGKALIS DALAM MENGUASAI TEKS REPORT - Iskandar, Joni; Delfi, Syofia; ', M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was designed to describe the student’s ability in comprehending report texts and aimed to find out the students ability in comprehending report texts for each component and the level of Bloom’s Revised Taxonomy indicated in the ability. This research took place in SMAN 1 Bantan Kabupaten Bengkalis that collected from February to April 2017. The try out class was XI IPS 3 (26 students) and the sample was XI IPA 1 (29 students) chosen by cluster random sampling. The result showed that the ability of the second year students of SMAN 1 Bantan in comprehending report texts for each component is in good level which the mean score was 60.0, however, the students have not passed the minimum score of the school which is 76. For the level of remembering; finding factual information the mean score was 73.4, finding references was 42.5, finding meaning of difficult words was 42.2. The level of understanding (finding restatement) the mean score was 62.0, for the analyzing level (finding main idea) the mean score was 72.7. and the level of evaluating (finding social function) was 64.8. Therefore, this research suggested the English teachers to focus on the level and components that students still find difficulities and categorized them into poor level. Students should learn the components in report texts and other text types. Further researchers are expected to find the standard guidance of classification of Bloom’s Revised Taxonomy indicated the components of reading comprehension.Key Words: Student’s Ability, Bloom’s Revised Taxonomy, Comprehending Report Texts.